APPRAISAL OF QUALITATIVE AND PRODUCTIVE ENTREPRENEURSHIP EDUCATION FOR SUSTAINABLE NATIONAL DEVELOPMENT IN NIGERIA - Danbuba, Jummai Muhammad (Sokoto Educational Review, 2017)
The unemployment rate demands for the re-positioning of our educational policies and programmes in the production of self-reliant graduates that will not only be independent but employers of labour. This paper sought to examine the objectives of entrepreneurship education in terms of empowerment, diversification and job creation, as well as the significance of the discipline in incorporating skills, integrating of economic models, professionalism, and entrepreneurship ethos. The paper further addressed the challenges that bedeviled entrepreneurship education such as lack of standard system on curriculum provision and evaluation, insecurity, and poor perception of the discipline with suggestions such as collaborative curriculum drafting, employment of qualified teachers, and adequate supervision of facilities for effective learning and sustainability.